RETRACTED: Efficiency and genotypic quality potential of winter wheat grain in the central chernozem region - Dolgopolova Natalia; Eremenko Olga; Feoktistov Gennady; Vishnevetsky Denis (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001